2011
DOI: 10.1002/uog.8826
|View full text |Cite
|
Sign up to set email alerts
|

Uterine myomas during pregnancy: a longitudinal sonographic study

Abstract: Objective To evaluate volumetric changes of uterine myomas (fibroids) during pregnancy. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
73
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 19 publications
2
73
2
2
Order By: Relevance
“…Case reports in the literature describe the possibility of vaginal expulsion of fibroid after UAE (7). In addition, myoma commonly expand and enlarge during pregnancy (8).…”
Section: Discussionmentioning
confidence: 99%
“…Case reports in the literature describe the possibility of vaginal expulsion of fibroid after UAE (7). In addition, myoma commonly expand and enlarge during pregnancy (8).…”
Section: Discussionmentioning
confidence: 99%
“…De ViVo et al [10] revealed that the volume of uterine fibroids significantly increased during pregnancy. Rosati et al [11] showed that the uterine fibroid volume increased during the first trimester, did not continue to increase during the second and third trimesters, and decreased after birth.…”
Section: Effect Of Progesterone On Uterine Fibroids During Pregnancymentioning
confidence: 99%
“…Estrogen is claimed to be the principle hormone promoting uterine growth. 16 Progesterone is thought to be responsible for maintain the size of these tumors. 17 However, sex hormone did not seem to be the only hormones involved.…”
Section: Effect Of Pregnancy On Uterine Fibroidsmentioning
confidence: 99%
“…a linear relationship between fibroid growth rate and sex hormone secretion had never been established. 14,16 Although estrogen and progesterone increase steadily during pregnancy, fibroids shrink in size during second and third trimesters. 12,14,16,18 Therefore, authors argue a role of other hormones in fibroid growth during pregnancy particularly human chorionic gonadotropin (hCG).…”
Section: Effect Of Pregnancy On Uterine Fibroidsmentioning
confidence: 99%